Peningkatan Kapasitas Tim Pendamping Keluarga (TPK) dalam Melakukan Surveilan pada Program Percepatan Penurunan Stunting di Kabupaten Sragen - Mulyasari, Indri; Puji Afiatna; Moneca Diah Listiyaningsih; Anisa Puspitasari (UNIVERSITAS NGUDI WALUYO, 2024)
Nutrition surveillance data related to stunting is important as a basis for program formulation. The skills of the data collection team in nutrition surveillance determine the quality of the data. One of the roles of the family assistance team is to collect data using both interviews and anthropometric measurements. Lack of skill in collecting data can lead to misinterpretation, which can lead to ineffective nutrition programs. Training activities for family support teams related to interview techniques and anthropometric measurements were carried out to overcome these problems. The methods used were lectures, demonstrations, and simulations. The results of the activity are expected to improve the skills of the family support team in collecting nutrition surveillance data. After the activity, the knowledge of the family support team increased. The skills of the family support team still need to be refreshed regularly because there are still misperceptions related to interview techniques. In addition, anthropometric measurement errors were still found, especially in measuring mid-upper arm circumference and height. ABSTRAK Data surveilan gizi terkait stunting penting sebagai dasar perumusan program. Keterampilan tim pengumpul data dalam surveilan gizi menentukan kualitas data. Salah satu peran TPK adalah mengumpulkan data baik menggunakan metode wawancara maupun pengukuran antropometri. TPK yang kurang terampil dalam mengumpulkan data dapat menyebabkan interpretasi yang keliru yang dapat menyebabkan program gizi menjadi kurang efektif. Kegiatan pelatihan bagi TPK terkait teknik wawancara dan pengukuran antropometri dilaksanakan untuk mengatasi masalah tersebut. Metode yang digunakan adalah ceramah, demonstrasi, dan simulasi. Hasil kegiatan diharapkan dapat meningkatkan keterampilan TPK dalam mengumpulkan data surveilan gizi. Setelah kegiatan pengetahuan TPK meningkat. Keterampilan TPK masih perlu mendapatkan penyegaran secara berkala karena masih ditemukan kesalahan persepsi terkait teknik wawancara. Selain itu, masih ditemukan kesalahan pengukuran antropometri terutama pada pengukuran lingkar lengan atas dan tinggi badan.